Intra-EU Direct Investment and Enlargement - Andrea Festa (Review of Economic Perspectives, 2015)
This paper examines the determinants of the intra-EU direct investment (IDI) into the New Member States (NMS) using a panel dataset of bilateral capital flows for the period 1993-2013. It is found out by using a simple gravity model that EU membership is the most important determinant. Unlike previous studies including non-EU countries, the distance is insignificant, which is caused by proximity of these countries to one another. A separate analysis focused on subgroups of accession countries gives some evidence that even when size of their economy, distance, institutional quality and EU accession are taken into account, Central European countries receive more IDI than the Baltic and the Balkan states. On the contrary to that, the analysis restricted to the Balkan countries which have joined the EU shows the inexistence of a negative Balkans effect in attracting foreign investment. This finding is relevant because previous studies demonstrate a persistent negative Balkans effect for non-EU Balkan countries and suggests a crucial impact of the EU accession in determining the intra-EU capital flows.
Keywords: 330